2022
DOI: 10.3390/molecules27061755
|View full text |Cite
|
Sign up to set email alerts
|

The Antagonizing Role of Heme in the Antimalarial Function of Artemisinin: Elevating Intracellular Free Heme Negatively Impacts Artemisinin Activity in Plasmodium falciparum

Abstract: The rich source of heme within malarial parasites has been considered to underly the action specificity of artemisinin. We reasoned that increasing intraparasitic free heme levels might further sensitize the parasites to artemisinin. Various means, such as modulating heme synthesis, degradation, polymerization, or hemoglobin digestion, were tried to boost intracellular heme levels, and under several scenarios, free heme levels were significantly augmented. Interestingly, all results arrived at the same conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…[121][122][123][124][125][126][127][128] The Fe(II)-Heme is reported to play a role in the cleavage. [129][130][131] So, it is fair to expect that the development of artemisinin-ferrocene conjugates could enhance the activity of artemisinin as the redox-active Fe-centre can catalyze the indo-peroxide link cleavage. To improve the antimalarial efficacy of artemisinin, Dive et al synthesized four artemisinin-ferrocene conjugates (36-39) (37, 38 have α and β anomers) following the synthetic route shown in Figure 10.…”
Section: Antimalarial Activity Of 3 D Metal-based Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…[121][122][123][124][125][126][127][128] The Fe(II)-Heme is reported to play a role in the cleavage. [129][130][131] So, it is fair to expect that the development of artemisinin-ferrocene conjugates could enhance the activity of artemisinin as the redox-active Fe-centre can catalyze the indo-peroxide link cleavage. To improve the antimalarial efficacy of artemisinin, Dive et al synthesized four artemisinin-ferrocene conjugates (36-39) (37, 38 have α and β anomers) following the synthetic route shown in Figure 10.…”
Section: Antimalarial Activity Of 3 D Metal-based Complexesmentioning
confidence: 99%
“…The endo‐peroxide linkage present in artemisinin breaks homolytically resulting in ROS generation [121–128] . The Fe(II)‐Heme is reported to play a role in the cleavage [129–131] . So, it is fair to expect that the development of artemisinin‐ferrocene conjugates could enhance the activity of artemisinin as the redox‐active Fe‐centre can catalyze the indo‐peroxide link cleavage.…”
Section: Antimalarial Activity Of 3 D Metal‐based Complexesmentioning
confidence: 99%
“…This toxic by-product of parasite protease-mediated hemoglobin degradation is thought to be the primary activator of ART [ 19 ]. While disruption of the heme-degradation process decreases parasite sensitivity to ART, a recent study provided evidence that increasing heme levels also selectively antagonized ART’s antimalarial action, suggesting a multifactorial relationship between the heme-detoxification pathway and ART activation [ 20 ].…”
Section: Artemisinin Mode Of Action and Mechanism Of Resistancementioning
confidence: 99%
“…The heme molecule is considered a possible target (but probably not the sole target) of artemisinin-derived endoperoxides and analogous compounds [ 122 ]. Nevertheless, the role of heme is complex, and a recent study revealed that too much heme is not good for the antimalarial action of artemisinins [ 123 ]. The mechanism of action of artemisinin is pluri-factorial.…”
Section: Mechanism Of Action Of Yingzhaosu Amentioning
confidence: 99%